Heat capacity of methane-krypton solid solutions. Conversion effect - Minchina, I.Ya.; Manzhelii, V.G.; Bagatskii, M.I.; Sklyar, O.V.; Mashchenko, D.A.; Pokhodenko, M.A. (Физика низких температур, 2001)
The heat capacity of Kr-nCH₄ solid solutions with the concentrations n= 1; 5; 10% and of the solid solution Kr-1%CH₄-0.2%O₂ has been studied at 0.7-8 K. The contributions of Crot to the heat capacity of the solutions caused by the rotation of the CH₄ molecules are estimated. The deviations of the measured Crot from the values corresponding to the equilibrium distribution of the nuclear spin CH₄ modifications are dependent on the correlation between the characteristic times of conversion and of the calorimetric experiment. The effects of temperature, O₂ impurities, and CH₄ clusters upon the conversion rate are studied. It is shown that the hybrid mechanism of conversion proposed by Berlinsky and Nijman, which takes into account both intramolecular and intermolecular interactions of the proton spins, is predominant.